Ocular complications in diabetes - Rodríguez S., César A. (1957)
The high morbidity rate in the current epoch represents diabetes in all countries of the world, is a medical problem not only as a major mortality factor, but as a cause of disability and inability to cope with the needs of modern life. Poor vision, generalized vascular lesions with diabetic nefropatío, have become issues of concern to all physicians.